Biocrude Production through Pyrolysis of Used Tyres. (14th May 2014) - Osayi, Julius I.; Iyuke, Sunny; Ogbeide, Samuel E.
Abstract : A review of the pyrolysis process of used tyre as a method of producing an alternative energy source is presented in this paper. The study reports the characteristics of used tyre materials and methods of recycling, types and principles of pyrolysis, the pyrolysis products and their composition, effects of process parameters, and kinetic models applied to pyrolysis. From publications, the proximate analysis of tyre rubber shows that it is composed of about 28.6 wt.% fixed carbon, 62 wt.% volatile material, 8.5 wt.% ash, and 0.9 wt.% moisture. Elemental analysis reveals that tyre rubber has an estimated value of 82 wt.% of C, 8 wt.% of H, 0.4 wt.% of N, 1.3 wt.% of S, 2.4 wt.% of O, and 5.9 wt.% of ash. Thermogravimetry analysis confirms that the pyrolysis of used tyre at atmospheric pressure commences at 250°C and completes at 550°C. The three primary products obtained from used tyre pyrolysis are solid residue (around 36 wt.%), liquid fraction or biocrude (around 55 wt.%), and gas fraction (around 9 wt.%). Although there is variation in the value of kinetic parameters obtained by different authors from the kinetic modeling of used tyre, the process is generally accepted as a first order reaction based on Arrhenius theory.